Analysis Of Digital Tafsir Literacy Competencies Among The Students Of Banten State Islamic University - Febriani, Ina Salmah; Masfuah, Utami Syifa; Ulyanti, Ahya (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
This article explored how digital tafsir competencies in Islamic Religious Education Program Of Banten State Islamic University. This research was conducted in June-August 2023. Respondents were PAI students in V semester who had received Tafsir Tarbawi and 'Ulumul Quran Subject as many as 121 students. The methodology used is descriptive qualitative. Researchers tried to descriptively described how digital tafsir literacy abilities are. The data collection process was carried out by distributing questions (gform) related to questions regarding digital tafsir. From the results of data analysis, it was found that as many as 65% of PAI Study Program students had sufficient knowledge in utilizing digital tafsir literature to find reference sources, however they still used various online media sites to search for quoting the Quran. Next, as many as 20% of students do not have sufficient skills to utilize digital tafsir. Lastly, as many as 15% of students do not have the skills to look for reference sources, their quota is still used for entertaint affecting their daily behavior.